Могильники варварского населения Крыма I-V вв. - Мульд, С.А. (Материалы по археологии, истории и этнографии Таврии, 1996)
Могильники Крыма I-V вв. н.э. можно разделить на три группы. Самая ранняя оставлена населением позднескифского государства. Две другие связаны с появлением в III в. на полуострове германцев и алан. The author has divided cemeteries into three groups. The earliest one is attributed to the population of Late-Scythian state. Two other groups are related to the period of arrival of Germanic and Alanic tribes to the peninsula in the 3d century A.D. Burial rites charecteristic to each group of the cemeteries are examined in this article.